3D Printing of Tough Hydrogel Scaffolds with Functional Surface Structures for Tissue Regeneration - Yao, Ke; Hong, Gaoying; Yuan, Ximin; Kong, Weicheng; Xia, Pengcheng; Li, Yuanrong; Chen, Yuewei; Liu, Nian; He, Jing; Shi, Jue; Hu, Zihe; Zhou, Yanyan; et al. (Nano-Micro Letters, 2024)
Hydrogel scaffolds have numerous potential applications in the tissue engineering field. However, tough hydrogel scaffolds implanted in vivo are seldom reported because it is difficult to balance biocompatibility and high mechanical properties. Inspired by Chinese ramen, we propose a universal fabricating method (printing-P, training-T, cross-linking-C, PTC & PCT) for tough hydrogel scaffolds to fill this gap. First, 3D printing fabricates a hydrogel scaffold with desired structures (P). Then, the scaffold could have extraordinarily high mechanical properties and functional surface structure by cycle mechanical training with salting-out assistance (T). Finally, the training results are fixed by photo-cross-linking processing (C). The tough gelatin hydrogel scaffolds exhibit excellent tensile strength of 6.66 MPa (622-fold untreated) and have excellent biocompatibility. Furthermore, this scaffold possesses functional surface structures from nanometer to micron to millimeter, which can efficiently induce directional cell growth. Interestingly, this strategy can produce bionic human tissue with mechanical properties of 10 kPa-10 MPa by changing the type of salt, and many hydrogels, such as gelatin and silk, could be improved with PTC or PCT strategies. Animal experiments show that this scaffold can effectively promote the new generation of muscle fibers, blood vessels, and nerves within 4 weeks, prompting the rapid regeneration of large-volume muscle loss injuries. Highlights: 1 We propose the novel concept of a tough hydrogel scaffold within the realm of tissue engineering. This scaffold combines exceptional strength (6.66 MPa), customization capabilities, and superior biocompatibility in a manner not previously achieved in existing research. 2 These tough hydrogel scaffolds possess functional surface structures and can effectively enhance cell-guided growth and prompt regeneration of muscle tissue in vivo. 3 This is a universal manufacturing method for tough hydrogel scaffolds in tissue engineering.